Expansion of natural killer cells but not T cells in human interleukin 2/interleukin 2 receptor (Tac) transgenic mice (The Rockefeller University Press, 1989)
Transgenic mice expressing both human IL-2 and the L chain of IL-2-R constitutively had an unusual expansion of Thy-1+/CD3-4-8- large granular lymphocytes, which bore the elevated NK activity. Unexpectedly, the transgenic mice had neither T cell expansion nor autoreactive antibodies. The increase in number and activity of NK cells seems to be responsible for both the severe interstitial pneumonia and lymphocyte depletion in the spleen that we found in these transgenic mice. In addition, we found the selective loss of Purkinje cells in the cerebellum of the mice, which gave rise to their disturbed gait. All the transgenic mice died by 4 wk of age.